2016
DOI: 10.1080/01904167.2016.1187739
|View full text |Cite
|
Sign up to set email alerts
|

Lettuce (Lactuca sativaL.) growth, yield and quality response to nitrogen fertilization in a non-circulating hydroponic system

Abstract: The objective of this study was to determine the effect of nitrogen fertilization rate on growth and quality of leafy lettuce grown during the winter season in non-circulating hydroponic system. Plants were subjected to seven nitrogen (N) concentrations, i.e. 0, 30, 60, 90, 120, 150 and 180 mg L -1 N using ammonium nitrate. Nitrogen treatments did not have a significant effect on leaf fresh and dry mass, root fresh and dry mass, number leaves and leaf area. Leaf ascorbic Downloaded by [University of California… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
27
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 30 publications
10
27
2
4
Order By: Relevance
“…In addition, the cubic effect was observed because yield began to decrease when N concentration increased from 150 to 200 mg · L -1 but increased again with increasing N concentration from 300 to 400 mg · L -1 . These results are consistent with earlier findings for lettuce in a hydroponic system (Fallovo et al, 2009;Mahlangu et al, 2016) and in field condition (Di Gioia et al, 2017). With wider ranges of nutrient solution N concentration (40-2400 mg · L -1 ), Stefanelli et al (2011) observed increase in oak leaf yield grown with perlite substrate to a maximum level at 400 mg · L -1 but there was no statistical difference in yield between N rates at 400 mg · L -1 and the commercial standard rate (1000-1200 mg · L -1 ) used in the region (Australia).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, the cubic effect was observed because yield began to decrease when N concentration increased from 150 to 200 mg · L -1 but increased again with increasing N concentration from 300 to 400 mg · L -1 . These results are consistent with earlier findings for lettuce in a hydroponic system (Fallovo et al, 2009;Mahlangu et al, 2016) and in field condition (Di Gioia et al, 2017). With wider ranges of nutrient solution N concentration (40-2400 mg · L -1 ), Stefanelli et al (2011) observed increase in oak leaf yield grown with perlite substrate to a maximum level at 400 mg · L -1 but there was no statistical difference in yield between N rates at 400 mg · L -1 and the commercial standard rate (1000-1200 mg · L -1 ) used in the region (Australia).…”
Section: Discussionsupporting
confidence: 93%
“…Because a continuous supply of N in the nutrient solution is a prerequisite for normal growth, the ensuing critical question is as follows: what is the optimum N concentration to use in the nutrient solution to ensure maximum growth and yield? The current literature reports a wide range of N concentration for maximum growth and yield in hydroponic lettuce production systems (Fallovo et al, 2009;Mahlangu et al, 2016;Resh, 2012;Stefanelli et al, 2011). Gent (2014) reported that concentrations of nitrate in standard nutrient solutions for hydroponics range from 100 to 200 mg · L -1 .…”
mentioning
confidence: 99%
“…In other plant species, high correlation between the two variables was demonstrated, as in oregano (r= 0.64) (Medellí n et al, 2016) and kaki (r= 0.97) (Choi et al, 2011). In general, these studies proved that SPAD has strong correlations with the N content in the leaf, which correlated with increased photosynthesis and productivity, as observed by Mahlangu et al (2016). This reaffirms the efficiency of the SPAD chlorophyll meter for diagnosing the N level in jambu plants, as well as for predicting yield, as observed by Milagres et al (2018) in potato cultivation.…”
Section: Correlation Of Thementioning
confidence: 76%
“…The N are related to various plant physiological process, acting in significant manner at the photosynthesis, respiration, ionic absorption and other process related to growing and development vegetal (Mahlangu et al, 2016;Marschner, 2012;Taiz et al, 2017). In general, vegetables have large necessity of N due to your short cycle, as demonstrated in lettuce studies, jambu same family specie (Mahlangu et al, 2016).…”
Section: Leaf Dry Massmentioning
confidence: 99%
“…Lettuce leaves were oven dried at 70°C for 48 hr and thereafter ground and sieved to quantify the leaf N, P, K, Ca, Mg, Zn, and Fe content using the ICP OES (inductively coupled plasma optical emission spectrometry) according to Mahlangu, Maboko, Sivakumar, Soundy, and Jifon (2016).…”
Section: Mineral Analysismentioning
confidence: 99%